Challenging diagnoses of tetraploidy/diploidy and trisomy 12: utility of first-tier prenatal testing methods - Iordanescu, Irina Ioana; Neacsu, Anca Teodora; Catana, Andreea; Barabas-CuzmicI, Zina; Suciu, Viorel; Dragomir, Cristina; Voicu, Diana Elena; Severin, Emilia; Militaru, Mariela Sanda (Frontiers in Genetics, 2023)
Chromosome mosaicism and low-grade mosaicism presents a challenge for diagnosis in the era of SNP array and NGS. Tetraploidy is a rare numerical chromosomal abnormality characterized by the presence of four copies of each chromosome. The prevalence of tetraploidy/diploidy mosaicism cases is extremely rare in the human population. Accurate estimates of the frequency of this chromosomal anomaly are lacking due to its classification as an extremely rare and difficult-to-detect condition. In this report, we describe two cases involving challenging diagnoses of tetraploidy/diploidy and trisomy 12. Additionally, we discuss the utility of first-tier prenatal testing methods such as SNP array compared to conventional G band karyotyping.